IMAGING OF PERSISTENT BRAIN DAMAGE FROM HYPERTENSIVE ENCEPHALOPATHY IN A CHILD WITH NEUROPSYCHIATRIC SYSTEMIC LUPUS ERYTHEMATOSUS (NPSLE) AND ALFA THALASSEMIA TRAIT, A CASE REPORT. - HIRUNPAT, Siriporn; VACHVANICHSANONG, Prayong; HIRUNPAT, Chakree (The ASEAN Journal of Radiology, 2023)
An unusual case ofa neuropsychiatric systemic lupus erythematosus (NPSLE) child with hypertensive encephalopathy is presented. Despite the rare presentation of hypertensive encephalopathy in children, characteristic lesions in the brain should be recognized as possible manifestation of this condition. In contrast to other reports in which the brain damage was almost always reversible, we present a serial follow up images which demonstrate both reversible and irreversible brain damages. Brain lesions associated with hemorrhage, which MAY - AUG. 2004. Volume X Number II are seldom described in most reports, have less likelihood reversibility.